THE INTEGRAL CONNECTION BETWEEN EASTERN AND WESTERN PHILOSOPHY - Qiyom Nazarov (American Journals Publishing, 2025)
The article analyzes issues related to the interconnectedness of Eastern and Western philosophy.
Keywords: East, West, Eastern philosophy, Western philosophy, Interrelation of Eastern and Western philosophy.